2008
DOI: 10.1590/s1413-35552008000400004
|View full text |Cite
|
Sign up to set email alerts
|

Aprimoramento da capacidade funcional de idosos submetidos a uma intervenção por isostretching

Abstract: Objective: To investigate the improvement in functional capacity among elderly people undergoing an isostretching intervention.Methods: This study sample was composed of 39 elderly people of both genders who were sedentary, clinically healthy and aged 66.3±3.34 years. They were divided into two groups: control group (n=19) and experimental group (n=20). The experimental group underwent a ten-session intervention based on isostretching (which is classified as a postural method), applied once a week. Functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
25

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 26 publications
(23 reference statements)
0
2
0
25
Order By: Relevance
“…The application of this method has been studied for different purposes, such as: evaluating respiratory consequences in healthy individuals (7), optimization of skills in athletes (8), improvement of gait (9) and balance (10,11,12), functional capacity in the elderly (12,13), hamstring lexibility (14), posterior chain muscles (15), the bene its in patients with shoulder impingement syndrome (16) and mastectomy (17). Still, with respect to speci ic applications in postural re-education, studies were found with this technique in the treatment of idiopathic scoliosis (18,19,20,21) and thoracic kyphosis (22).…”
Section: Introductionmentioning
confidence: 99%
“…The application of this method has been studied for different purposes, such as: evaluating respiratory consequences in healthy individuals (7), optimization of skills in athletes (8), improvement of gait (9) and balance (10,11,12), functional capacity in the elderly (12,13), hamstring lexibility (14), posterior chain muscles (15), the bene its in patients with shoulder impingement syndrome (16) and mastectomy (17). Still, with respect to speci ic applications in postural re-education, studies were found with this technique in the treatment of idiopathic scoliosis (18,19,20,21) and thoracic kyphosis (22).…”
Section: Introductionmentioning
confidence: 99%
“…Os exercícios são executados com alinhamento vertebral máximo, exigindo da coluna uma atitude de autoalongamento. Assim, o método promove consciência corporal e aprimora o controle neuromuscular, a lexibilidade, a mobilidade articular, a tonicidade, a força e o controle respiratório, já que a base do método é a respiração focada principalmente na expiração (12). Embora esse recurso terapêutico seja habitualmente utilizado no meio clínico, ainda são relativamente poucos os estudos bem conduzidos que justi icam o seu uso, inclusive na lombalgia crônica.…”
Section: Caracterização Da Amostra E Divisão Dos Gruposunclassified
“…Já para a determinação da Pemáx, realizou-se uma expiração máxima a partir da capacidade pulmonar total. Nos dois testes, foram registradas as pressões h) cada postura foi previamente demonstrada pelo pesquisador/instrutor antes da execução pelas voluntárias; i) o pesquisador/instrutor corrigiu, por meio de estímulo verbal e/ou tátil, as voluntárias que eventualmente não estivessem executando o exercício da forma correta (12).…”
Section: Procedimento De Intervençãounclassified
“…Esses subsistemas, sob condições normais, garantem a estabilidade estática e dinâmica da coluna (1). Além de ser um componente importante para prover uma base sólida e exercer ou resistir às forças, o aperfeiçoamento da estabilidade segmentar e do controle neuromuscular do tronco pode proporcionar melhores condições biomecânicas (2).…”
Section: Introductionunclassified